Estudo de mecanismos de toxicidade do metilmercúrio: papel protetor de flavonóides - Wagner, Caroline (2010)
Methylmercury (MeHg) is an important environmental toxicant that may cause irreversible neurobehavioral and neuropsychological disorders in humans and experimental animals. The major mechanisms of MeHg-induced toxicity currently being explored are the disruption of intracellular calcium homeostasis, the induction of oxidative stress, inhibition of neuronal Na+/K+ -ATPase activity and change the status of antioxidant systems. In addition, recent data reported the involvement of MeHg toxicity with damage in thioredoxin system. On the other hand, flavonoids have been reported to possess divalent metal chelating properties, antioxidant activities and to readily permeate the blood brain barrier. They can also provide neuroprotection in a wide array of cellular and animal models of neurological diseases, including protection against MeHg toxicity. However, the exact mechanism of MeHg toxicity remain unclear and limited data on the interaction of MeHg with flavonoids are avaliable in literature. In view of this, our study evaluated the mechanisms of MeHg toxicity in vivo and in vitro models and evaluated the performance of different flavonoids: quercetin, quercitrin and rutin in diferent models of MeHg toxicity. Our study showed that MeHg (100 μM) caused lipid peroxidation and reactive oxygen species (ROS) generation in brain cortical slices. Quercitrin and quercetin protected against this toxicity and mitochondria from MeHg (5 μM)-induced ROS generation. In contrast, rutin did not afford a significant protective effect against MeHg (100 μM)-induced lipid peroxidation and ROS production in cortical brain slices. MeHg-generated ROS in cortical slices was dependent upon an increase in intracellular calcium levels. In vivo studies with mice treated during 30 days with MeHg (5mg/Kg) orally, presented a marked increase in toxicity parameters (loss in body weight gain, increased in micronucleis frequencies, nefrotoxicity), decrease in motor system performance (locomotor activity and motor coordination) and spatial memory deficiency as well as alteration in some biochemical parameters (decrease in glutathione peroxidase and Na+/K+ ATPase activity, increase in lipid peroxidation). The co-treatment with quercitrin (10mg/kg) intraperitoneally, decreased the behavior alterations manly by decreased lipid peroxidation levels, maintained the Na+/K+ ATPase and GPx activities. In addition, our study demonstrated, for the first time, that MeHg inhibited the activity of thioredoxin reductase. A single oral MeHg administration (1, 5 and 10 mg/Kg) caused a marked inhibition of kidney TrxR, while in liver a significant inhibition was observed after exposure to 5 and 10 mg/Kg of MeHg (TrxR was determined 24 hours after MeHg). In brain, MeHg did not inhibit TrxR. In vitro results demonstrated that MeHg inhibited brain (0.05 1 μM) , liver (0.05 1 μM) and kidney (0.025 1 μM) TrxR in a dose dependent manner Here, we have extended the characterization of mechanisms associated with the neuroprotective effects of flavonoids quercetin and quercitrin against MeHg-induced toxicity. In addition, we provided novel data establishing that (1) calcium plays a central role in MeHg toxicity, (2) in brain slices MeHg induces mitochondrial oxidative stress both via direct interaction with mitochondria as well as via mitochondria- indirect mechanisms. In addition (3) MeHg (5mg/kg) caused a number of behavioural alterations that are related with an inhibition of cerebelar and cerebral GPx and Na+/K+ ATPase activities and (4) increased in lipid peroxidation.The higly affinity of MeHg to selenol groups of endogenous molecules can lead to (5) inhibition of thioredoxin reductase that can contribute to MeHg toxicity. We conclude that MeHg lead to increase in mitochondria ROS generation that contributes to increase in lipid peroxidation. In addition, the inhibition of important antioxidant enzymes such as GPx ans TrxR can contribute to oxidative damage that can be related to development of behavioral damage. In this view the antioxidant activity of flavonoids quercetin and quercitrin seems to be direct associate with the capacity of flavonoids to confere protection against MeHg toxicity.